Perencanaan Struktur Gedung Asrama Mahasiswa Universitas Sriwijaya Palembang Dengan Penahan Lateral Kombinasi Sistem Rangka Pemikul Momen Dan Dinding Struktural - Sendi Septian Rian Sanjaya (Jurusan Teknik Sipil Fakultas Teknik Universitas Sriwijaya, 2014)
Indonesia is an earthquake prone areas, to reduce the risk of the disaster required the construction of earthquake resistant buildings. The structure usually design base on the elastic analysis that would be multiplied by load factor to simulate the ultimate condition. Actually, the behavior of building subject to seismic loads are in-elastic. Concrete structure is the most commonly material in the construction. In high-rise buildings quake resistant, generally the forces at column is enough to resist the quake loads so need to use rigid structural elements such as shearwall to resist combined shear force, moment and axial force due to earthquake. With using shearwall, the majority of quake loads will be absorbed by shearwall.Â This essay took the topic about Sriwijaya University dorm building with lateral resistant combined moment resisting frame system and shearwall. Building were designed according to SNI 03-2847-2002 and SNI 03-1726-2002. From the result of the calculation have been done, the result is dimension and rebar reinforcement of the struktural elements. Beam dimension 25 x 40 cm, column dimension 40 x 40 cm, slab thickness 16 cm and shearwall thickness 25 cm. Joint displacement deviation due to x axis quake load and y axis quake load is 5,52 mm and 5,71 mm, where that result not exceed service limit and ultimate limit of building. Â Key Words : earthquake, concrete, lateral resistant, mrfs, shearwall